EPISENTRUM KESIAPSIAGAAN: PERAN SENTRAL RESILIENCE HUB KOMUNITAS DALAM KOMUNIKASI RISIKO BENCANA TSUNAMI DI DESA PANGGARANGAN, INDONESIA - Fakhruddin, Irwan; Sylviana Mirahayu , Ifani; Rani, Hedista; Mauldina, Siti Fifthya (Jurnal Netnografi Komunikasi, 2025)
Indonesia's geographical position exposes it to high vulnerability to geological and hydrometeorological disasters, demanding a solid disaster risk reduction (DRR) framework. The disaster management paradigm is now shifting from a merely reactive response towards proactive resilience-building. Disaster risk education is a key element in this transition; however, many initiatives are still top-down and often neglect the vital role of community-owned spaces. This article investigates the function of educational space as critical infrastructure for disaster risk communication in Panggarangan Village, Banten, the first village in its province to achieve the ‘Tsunami Ready Community’ recognition from UNESCO-IOC. Employing a qualitative-observatory case study method, this research maps the interaction between actors, various activities, and the spaces that accommodate disaster education activities. The main findings indicate a pentahelix collaboration model significantly dominated by community actors, particularly the South Lebak Mitigation Group (GMLS). The key to their success rests on the existence of a ‘resilience hub’—namely the GMLS Command Center in the Villa Hejo Kiarapayung area—which serves as the primary location for the majority of educational activities. This research concludes that there is a strong consistency between the central role of community actors and the availability of a dedicated and easily accessible resilience hub. The success of Panggarangan suggests that the provision of community-centered spaces is a crucial—and often overlooked—factor in creating sustainable community-based disaster risk management (CBDRM). Keywords: Community-Based Disaster Risk Management (CBDRM), Disaster Risk Communication, Resilience Hub, Educational Space, Tsunami Preparedness.